Impacts of supplementation of probiotics on the prevalence of grape marc derived polyphenols in colonic digesta using in vitro digestion model. (October 2019) - Li, M J; Loo, Y T; Cheng, L; Howell, K; Zhang, P Z
Abstract: Grape marc is a by-product of winemaking that contains numerous polyphenols, the bioavailability of polyphenol is largely dependent on their metabolism by probiotics or gut microbiome. The two-way phenolic-microbiota interaction has been postulated as the microorganisms and specific polyphenols could affect each other and exert beneficial effects on the host health. However, the oral taken probiotics showed a low survival rate in the gastrointestinal tract, while using encapsulation technique can provide them with a protective microenvironment. The objective of this study was to investigate the bioaccessibility of polyphenols originated from whole grape marc, consisting of seeds, skins and stems, combined with encapsulated oral taken probiotics, using in vitro digestion model and analytical chemistry techniques. 23 phenolic compounds were evaluated in this study, which included phenolic acids, anthoxanthins and stilbenes. This study showed that the encapsulated probiotics were protected by microcapsules until being liberated in the large intestine, and the metabolism of some polyphenols derived from selected grape marc samples was promoted by probiotics. These results indicate the potential of combining grape marc polyphenols with probiotics to develop a new health product. Furthermore, this provides the wine industry with an opportunity to make a profit by using by-products.